An engineering thermodynamic approach to select the electromagnetic wave effective on cell growth. (21st September 2017) - Lucia, Umberto; Grisolia, Giulia; Ponzetto, Antonio; Silvagno, Francesca
Highlights: Cancer is a noncontrol growth system. Cell life is the optimisation between power generation and heat exchange with environment. A control system of cancer growth is suggested by controlling energy balance. A new elf interaction is proved to control the energy balance. Consequently cancer growth is reduced. Abstract: To date, the choice of the characteristics of the extremely low-frequency electromagnetic field beneficial in proliferative disorders is still empirical. In order to make the ELF interaction selective, we applied the thermodynamic and biochemical principles to the analysis of the thermo-chemical output generated by the cell in the environment. The theoretical approach applied an engineering bio-thermodynamic approach recently developed in order to obtain a physical–mathematical model that calculated the frequency of the field able to maximize the mean entropy changes as a function of cellular parameters. The combined biochemical approach envisioned the changes of entropy as a metabolic shift leading to a reduction of cell growth. The proliferation of six human cancer cell lines was evaluated as the output signal able to confirm the correctness of the mathematical model. By considering the cell as a reactive system able to respond to the unbalancing external stimuli, for the first time we could calculate and validate the frequencies of the field specifically effective on distinct cells.